2010
DOI: 10.1089/adt.2009.0232
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Label-Free Biosensors for Pharmacological Screening With Cell-Based Functional Assays

Abstract: The diversity and impact of label-free technologies continues to expand in drug discovery. Two classes of label-free instruments, using either an electrical impedance-based or an optical-based biosensor, are now available for investigating the effects of ligands on cellular targets. Studies of GPCR function have been especially prominent with these instruments due to the importance of this target class in drug discovery. Although both classes of biosensors share similar high sensitivity to changes in cell shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…This study demonstrated that the PTX-sensitive G i/o subunits, especially G o and G i3 , play important roles in the activation of ERK evoked by amitriptyline. The CellKey TM assay confirmed the pharmacological and siRNA findings, in that the pattern of the change in impedance induced by amitriptyline was similar to that of activation of G i/o -coupled receptors, and not of G s -or G q -coupled receptors (13,14,17,18). Although the C6 cells is an astrocyte model cell line derived from rat glioma, activation of the MMP/FGFR/FRS2␣/ERK cascade occurs in both normal human and rat astrocytes as well (9,11), in a PTX-sensitive manner.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study demonstrated that the PTX-sensitive G i/o subunits, especially G o and G i3 , play important roles in the activation of ERK evoked by amitriptyline. The CellKey TM assay confirmed the pharmacological and siRNA findings, in that the pattern of the change in impedance induced by amitriptyline was similar to that of activation of G i/o -coupled receptors, and not of G s -or G q -coupled receptors (13,14,17,18). Although the C6 cells is an astrocyte model cell line derived from rat glioma, activation of the MMP/FGFR/FRS2␣/ERK cascade occurs in both normal human and rat astrocytes as well (9,11), in a PTX-sensitive manner.…”
Section: Discussionsupporting
confidence: 67%
“…The effect of amitriptyline on G protein activation in living C6 cells and rat astrocytes was analyzed using a novel biosensor technology, the CellKey TM assay (MDS Sciex, Ontario, Canada). The CellKey TM assay utilizes cellular dielectric spectroscopy, which is specifically tailored to G protein-coupled receptor (GPCR) detection and can distinguish signals between the G␣ s (G s ), G␣ i/o (G i/o ), and G␣ q (G q ) subfamilies (13,14).…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%
“…Cellular dielectric spectroscopy (CDS) is a novel technology that utilizes a label-free, real-time and cell-based assay approach and enables comprehensive pharmacological evaluation of cells that exogenously or endogenously express receptors (20,21). This technology is universal and allows the measurement of multiple types of receptors, including GPCRs, tyrosine kinase receptors, and nuclear receptors on the same platform without any modification of the cells (20,21).…”
Section: A Novel Assay For Gpcrs Using Cellular Dielectric Spectroscopymentioning
confidence: 99%
“…This technology is universal and allows the measurement of multiple types of receptors, including GPCRs, tyrosine kinase receptors, and nuclear receptors on the same platform without any modification of the cells (20,21). CDS is classified into two types, an optical-based biosensor and an electrical impedance-based biosensor (3).…”
Section: A Novel Assay For Gpcrs Using Cellular Dielectric Spectroscopymentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Conventional systems employ a stationary array of fiber optics to repetitively scan a microtiter plate. 12 As a result, only cells along the scanning path ͑ϳ100 m in width͒ are sampled to generate an averaged response.…”
mentioning
confidence: 99%